In silico structural analysis, physicochemical characterization and homology modeling of Arabidopsis thaliana Na+/H+ exchanger 1 protein - Feisal, Mohammad Rafid (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Biotechnology, 2015.